Organización de Eventos - HO138 - 202302 - Velapatiño Castro, María Ysabel (2023)
Description: Nowadays, events are considered experiences in which the organization, concept, provider selection and operation, as well as the coordination with the client, become visible in the staging. They seek to achieve integration, entertainment, communication, as well as business positioning. The course will allow students to master the processes, administrative tools, functions, and operational structure of the Events Organization Department as a key department of the Hotel. Students will learn that each event should be carried out with special emphasis on planning, teamwork, third-party quality control, and improvement proposals for management processes that will be of outmost importance for their professional performance since it will allow improving the productivity of a hotel's Events department. Purpose: This is a specific course of the Hospitality and Business Administration program, theoretical and practical in nature; aimed at seventh-term students, and seeks to develop the core competency of Innovative Thinking (Level 2) and the specific competencies ACPHA of Operational Management (Level 2) and Leadership (Level 2). A pre-requisite for this course is Food and Beverage Operation and Service.